روبورتاج مصور حول الشباب والامل بعنوان صناع الامل - حمزة, عفيفة (كلية العلوم الاجتماعية, 2020)
الملخص: الشباب هم عماد الامة وضامن لامنها و مستقبلها يتميزون بالقوة و الحيوية بطاقاتهم الجسدّية والعضلّية، وبأفكارهم الخّلّقة والإبداعية يسعون لبناء مجتمع متمثلّا بحضاراته، وإنجازاته، وتقدمه وتطوره، والدفاع عنه من خلّل القضايا العامة فيه لتحصيل الحقوق المختلفة لكافة شرائح المجتمع، كل هذه الميزات التي تحظى بها هذه الطاقة البشرية تجعل منها قادرة على أن تساهم في رسم خطى الامة نحو التقدم و التطور . فلو خصصنا الحديث عن الجزائر فيشكل هذا العنصر نسبة % 70من إجمالي التعداد السكاني ،فهم ثروة حقيقية تحظى بها البلّد اليوم و على مر الزمان ،فلو ألقينا نظرة للّمس سنجد في صفحات تاريخنا شباب تركوا بصماتهم من ذهب من خلّل تحدياتهم و مواجهتهم للمستعمر الغاشم في ثورة مباركة اقتلعت العدو المستعمر . ففي كل فترة كان لهذه الفئة مكانة هامة في المجتمع. ترتبط فكرة الريبورتاج الذي قمنا بإنجازه بموضوع الشباب ، هذه الفئة التي طالما عانت من التهميش و اللّمبالاة في بلّدنا على غرار كل المحاولات التي سعت فيها الدولة الجزائرية لاعطاء جانب من الاهتمام على مدار الفترات، الا انه لم يكن كافيا بالنظر لثروات و الامكانيات التي تحوز عليها البلّد ، مما جعلهم يعيشون مشاكلّ كثيرة في السنوات الأخيرة من التسعينات الى يومنا هذا دفعت بهم إلى حد اليأس و الاستسلّم الواقع المعاش بعدما أغلقت كل الأبواب و المنافذ في وجههم ،فلجئ البعض منهم الى الهجرة بحثا عن مستقبل أفضل ، هذا الامر جعل بعض القنواتالتلفزيونية الجزائرية هي الاخرى تسلط الضوء على هذه الفئة فتتناول فقط الجانب المادي من الموضوع فرسخت صورة نمطية واحدة في ذهن المشاهد بأن الشاب الج ازئري سطحي و نمطي ، و لم تركز على غرس روح التحدي و المبادرة في شبكاتها البرامجية ،في حين أن أنه توجد فئة أخرى التي رأت أن التغبير يبدأ منها و ليس من المحيط الخارجي لم تبقى مكتوفت الايدي بل حاربت بكل طاقتها العقلية و الجسدية الواقع المرير بإيجابية و تفاءل لتواجهه بمشاريعها التى حققتها على أرض الواقع بإمكانياتها البسيطة و المحدودة لتبرهن لاصحاب القرار انهم هم التغيير و المستقبل الواعد للبلّد. و هو الامر الذي دفعنا لاعداد هذا الريبورتاج الذي يركز على الجانب الايجابي في حياة الشباب من خلّل تقديم عينة من النماذج لشباب الطموح و الناجح في مدينة مستغانم. نتمى أن يكون في المستوى المطلوب و ينال إعجابكم Summary: Young people are the pillar of the nation and a guarantor of its security and its future. They are distinguished by strength and vitality, by their physical energy, and by their creative ideas, they strive to build a society represented by its civilizations, its achievements, its progress and development, and to defend it through public issues in it in order to attain the various rights of all segments of society, all these makes them capable of contributing to drawing the nation's path towards progress and development .they are a real wealth that the country enjoys today and over time. If we look yesterday, we will find in the pages of our history young people who left their fingerprints in gold through their challenges and confronting the brutal colonizer in a blessed revolution that uprooted the colonial enemy. In every period, this category had an important place in society: The idea of the reportage that we created is related to the issue of youth, this group that has long suffered from marginalization and indifference in our country Like all the attempts in which the Algerian state sought to give some attention Throughout the periods, it was not enough, given thewealth and capabilities of the country, which made them live in many problems in the last years from the nineties to the present day, which pushed them to the point of despair and surrender. The reality of living after all doors and windows were closed to them, so some of them resorted to immigration in search of a better future. This made some Algerian television channels also highlight this category, dealing only with the material side of the subject, and cementing one stereotype in the viewer's mind that the Algerian youth is superficial and stereotypical, and did not focus on instilling a spirit of challenge and initiative in their program networks. While there is another group that saw that change begins with in them and not from the outside environment, they did not remain idle, but rather fought with all their mental and physical energy the bitter reality positively and optimistically, The ideas they came up with will prove to the decision-makers that they are the change and promising future of the country. And this is what prompted us to prepare this reportage that focuses on the Positive side in the life of young people by providing a sample of models for ambitious and successful youth in Mostaganem.We hope that it is at the required level and you like it
توجد النسخة الرقمية للروبورتاج بالمكتبة
Keywords: صناع الامل؛الشباب والامل